Market behaviour: case studies of NASDAQ OMX Baltic - Stankevičienė, Jelena; Gembickaja, Natalija (Business, Management and Economics Engineering, 2012)
The paper examines market behaviour, defines the concept of behavioural finance and exhaustively analyzes the varying behaviour of market participants and occurring examples. The article deals with the issues of possible anomalies describing their main features. The conducted research is aimed at investigating two anomalies in the Baltic Stock Exchanges, including branches in Tallinn, Riga and Vilnius. The publication selects specific stocks listed in the equity market and analyzes their features. The obtained results are compared to discuss differences and characteristics of the markets. The paper also presents an original examination of the practical aspects of momentum and contrarian anomalies, underlies recommendations and helps financial market participants with a better understanding of the influence of anomalies from an economic perspective and with improving their competitiveness thus helping them to make appropriate decisions.